Ecological assessment of different electrokinetic remediation strategies: a pilot scale study - Yudith Vega Paramitadevi; Beata Ratnawati; Agus Jatnika Effendy; Syarif Hidayat; Mochamad Arief Budihardjo; Bimastyaji Surya Ramadan; Dimas Ardi Prasetya; Ivone Wulandari Budiharto (Brawijaya University, 2023)
The electrokinetic remediation method can function as a primary or secondary technology and can be applied in conjunction with other physical and biological methods, such as soil washing, phytoremediation, and bioremediation. Environmental impacts arising from the electrokinetic remediation process can be determined using life cycle assessment analysis (LCA) or other tools. This study compared the conventional electrokinetic remediation strategy with two hybrid strategies: electrokinetic-phytoremediation (EKR-Phyto) and electrokinetic-bioremediation (EKR-Bio). The environmental performance of the three strategies is then tested through LCA analysis. The database used was The Ecoinvent, and the freeware software used during the inventory stage was OpenLCA. The impact assessment stage was used in the Recipe I (2016) midpoints, Available Water Remaining (AWARE) midpoint, Intergovernmental Panel Climate Change (IPCC) midpoint (2003), UNEP Society of Environmental Toxicology (USEtox) midpoint, and cumulative energy demand midpoint. The significance of the analysis results was not obtained for the GWP parameter but for the freshwater eutrophication parameter. Among the three strategies, the EKR-Phyto strategy showed the highest significance in eutrophication but the lowest significance in land change. Substitution of chemical fertilizers into natural fertilizers in the EKR-Phyto strategy can be an opportunity for environmental sustainability. The highest impact for ecological analysis of the three strategies was EKR-Phyto in terms of GWP, the sum of primary energy, Acidification Potential (AP), and Photochemical Ozone Creation Potential (POCP).